Calming the Storm: Natural Immunosuppressants as Adjuvants to Target the Cytokine Storm in COVID-19 - Peter, Angela E.; Sandeep, B. V.; Rao, B. Ganga; Kalpana, V. Lakshmi (Frontiers in Pharmacology, 2021)
The COVID-19 pandemic has caused a global health crisis, with no specific antiviral to treat the infection and the absence of a suitable vaccine to prevent it. While some individuals contracting the SARS-CoV-2 infection exhibit a well coordinated immune response and recover, others display a dysfunctional immune response leading to serious complications including ARDS, sepsis, MOF; associated with morbidity and mortality. Studies revealed that in patients with a dysfunctional immune response, there is a massive cytokine and chemokine release, referred to as the ‘cytokine storm’. As a result, such patients exhibit higher levels of pro-inflammatory/modulatory cytokines and chemokines like TNFα, INFγ, IL-1β, IL-2, IL-4, IL-6, IL-7, IL-8, IL-9, IL-10, IL-12, IL-13, IL-17, G-CSF, GM-CSF, MCSF, HGF and chemokines CXCL8, MCP1, IP10, MIP1α and MIP1β. Targeting this cytokine storm is a novel, promising treatment strategy to alleviate this excess influx of cytokines observed at the site of infection and their subsequent disastrous consequences. Natural Iimmunosuppressant compounds, derived from plant sources like curcumin, luteolin, piperine, resveratrol are known to inhibit the production and release of pro-inflammatory cytokines and chemokines. This inhibitory effect is mediated by altering signal pathways like NF-κB, JAK/STAT, MAPK/ERK that are involved in the production and release of cytokines and chemokines. The use of these natural immunosuppressants as adjuvants to ameliorate the cytokine storm; in combination with antiviral agents and other treatment drugs currently in use presents a novel, synergistic approach for the treatment and effective cure of COVID-19. This review briefly describes the immunopathogenesis of the cytokine storm observed in SARS-CoV-2 infection and details some natural immunosuppressants that can be used as adjuvants in treating COVID-19 disease.